Distribution of Papa and Papg Variants Among Escherichia Coli Genotypes: Association with Major Extraintestinal Pathogenic Lineages - Fernandez-Yañez, V; Hidalgo-Hormazabal, C (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
The pyelonephritis-associated fimbria (P fimbria) is one of the most recognized adhesion determinants of extraintestinal pathogenic Escherichia coli strains (ExPECs). Twelve variants have been described for the gene encoding the P fimbria major structural subunit PapA and three variants for the gene encoding the adhesin subunit PapG. However, their distribution among the ExPEC diversity has not been comprehensively addressed. A complete landscape of that distribution might be valuable for delineating basic studies about the pathogenicity mechanisms of ExPECs and following up on the evolution of ExPEC lineages, particularly those most epidemiologically relevant. Therefore, we performed a massive descriptive study to detect the papA and papG variants along different E. coli genotypes represented by genomic sequences contained in the NCBI Assembly Refseq database. The most common papA variants were F11, F10, F48, F16, F12, and F7-2, which were found in significant association with the most relevant ExPEC genotypes, the phylogroups B2 and D, and the sequence types ST95, ST131, ST127, ST69, ST12, and ST73. On the other hand, the papGII variant was by far the most common followed by papGIII, and both were also found to have a significant association with common ExPEC genotypes. We noticed the presence of genomes, mainly belonging to the sequence type ST12, harboring two or three papA variants and two papG variants. Furthermore, the most common papA and papG variants were also detected in records representing strains isolated from humans and animals such as poultry, bovine, and dogs, supporting previous hypotheses of potential cross-transmission. Finally, we characterized a set of 17 genomes from Chilean uropathogenic E. coli strains and found that ST12 and ST73 were the predominant sequence types. Variants F7-1, F7-2, F8, F9, F11, F13, F14, F16, and F48 were detected for papA, and papGII and papGIII variants were detected for papG. Significant associations with the sequence types observed in the analysis of genomes contained in the NCBI Assembly Refseq database were also found in this collection in 16 of 19 cases for papA variants and 7 of 9 cases for the papG variants. This comprehensive characterization might support future basic studies about P fimbria-mediated ExPEC adherence and future typing or epidemiological studies to monitor the evolution of ExPECs producing P fimbria. © 2024 by the authors.